Negative active material, preparation method thereof, negative pole piece comprising negative active material, battery and electric device
By using graphite core and hard carbon coated negative electrode active materials in the battery, the problem of insufficient fast charging performance and cycle life of existing batteries is solved, and a combination of high energy density and good kinetic performance is achieved.
Patent Information
- Application Number
- CN202410129306.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-30
- Publication Date
- 2025-04-15
AI Technical Summary
Existing batteries have shortcomings in fast charging performance and cycle life, especially the energy density of fast charging hard carbon materials is not high and the cycle performance is not excellent.
Using negative electrode active materials including graphite core and hard carbon coating, in the cumulative distribution curve of R value obtained by laser microscopic confocal Raman spectrometer surface scanning mode, the cumulative distribution of R value R50 is 0.15-0.40, to improve ion charge exchange capacity and reduce side reactions.
The battery has high energy density, good dynamic performance and cycle performance, and improves fast charging performance and cycle life.
Smart Images

Figure CN119833584A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a negative electrode active material and a preparation method thereof, as well as a negative electrode plate, a battery and an electrical device containing the negative electrode active material. Background Art
[0002] With the continuous expansion of battery application fields, people have higher and higher requirements for the fast charging performance of batteries. As an important component of the battery, the performance of the negative electrode will affect the comprehensive performance of the battery. At present, the commonly used negative electrode active material for the negative electrode is graphite, but the fast charging performance of graphite is usually not good enough. Based on this, fast-charging negative electrode active materials have been developed, such as fast-charging hard carbon. The energy density of the battery assembled with fast-charging hard carbon is usually not high, and its cycle life is not good enough, which limits its practical application. Therefore, how to make the battery have good fast charging performance and cycle performance while having a higher energy density is still a difficulty in current battery development. The above statements are only used to provide background technical information related to the present application, and do not necessarily constitute prior art. Summary of the invention
[0003] The present application provides a negative electrode active material and a preparation method thereof, as well as a negative electrode plate, a battery and an electrical device comprising the negative electrode active material, which can enable the battery to have high energy density, good kinetic performance and cycle performance.
[0004] In the first aspect, the present application provides a negative electrode active material, comprising a core and a coating layer located on at least a portion of the surface of the core, the core comprising graphite, and the coating layer comprising hard carbon; in the cumulative distribution curve of the R value of the negative electrode active material obtained in the surface scanning mode of a laser microscopic confocal Raman spectrometer, starting from the lower limit, the R value R50 with a cumulative distribution of 50% is 0.15-0.40.
[0005] The R value of the negative electrode active material can characterize the degree of defect and disorder of the negative electrode active material. The cumulative distribution of the negative electrode active material is 50% of the R value R50 is 0.15-0.40, which can not only improve the charge exchange capacity of ions on the surface of the negative electrode active material, but also keep the side reactions on the surface of the negative electrode active material particles at a lower level. Therefore, the negative electrode active material provided in the embodiment of the present application can enable the battery to have high energy density, good kinetic performance and cycle performance.
[0006] In some embodiments, the cumulative distribution of the negative electrode active material is 50% of the R value R50 is 0.20-0.30. This can make the battery better have high energy density, good kinetic performance and cycle performance.
[0007] In some embodiments, among all R values obtained by the negative electrode active material, the number of R values R50 less than 50% of the cumulative distribution of the core accounts for less than or equal to 10%. Optionally, among all R values obtained by the negative electrode active material, the number of R values R50 less than 50% of the cumulative distribution of the core accounts for less than or equal to 6%.
[0008] The smaller the value is, the less the degree of uncoating of the negative electrode active material is, the higher the isotropy of the negative electrode active material is, and the more active sites of the negative electrode active material are at this time. Thus, the charge exchange ability of ions on the surface of the negative electrode active material is better, thereby further improving the kinetic performance of the negative electrode active material and the battery. In addition, the less uncoating degree of the negative electrode active material is, the less the co-embedding phenomenon of the electrolyte solvent during the cycle, thereby also allowing the battery to have better cycle performance.
[0009] In some embodiments, the R-value R50 of the core at 50% of the cumulative distribution is less than the R-value R50 of the coating layer at 50% of the cumulative distribution.
[0010] The cumulative distribution of 50% of the R value R50 of the coating layer of the negative electrode active material is large and the disorder is large, which can make the negative electrode active material and the battery have good kinetic performance; the cumulative distribution of 50% of the R value R50 of the inner core of the negative electrode active material is small and the disorder is small, which can make the negative electrode active material as a whole have a higher gram capacity and the battery have a higher energy density.
[0011] In some embodiments, the cumulative distribution of the coating layer is 50% of the R value R50 is 0.9-1.4. When the cumulative distribution of the coating layer is 50% of the R value R50 within the above range, the coating layer itself has good kinetic properties, which can improve the kinetic properties of the negative electrode active material and the battery; it can also make the negative electrode active material have a smaller specific surface area, thereby reducing battery side reactions and making the battery have good cycle performance.
[0012] In some embodiments, the core has a cumulative distribution of 50% R value R50 of 0.06-0.13. The core has a cumulative distribution of 50% R value R50 within the above range, which can make the battery have both high energy density and good kinetic performance.
[0013] In some embodiments, the mass of the coating layer is 0.3%-4.5% of the mass of the core, and can be 1%-3.2%. The mass ratio of the coating layer within the above range is conducive to the battery having high energy density, good dynamic performance and long cycle life.
[0014] In some embodiments, the difference between the volume distribution particle size Dv50 of the negative electrode active material and the volume distribution particle size Dv50 of the core is 1 μm-5.5 μm, and can be optionally 1.5 μm-4.2 μm. The difference between the volume distribution particle size Dv50 of the negative electrode active material and the volume distribution particle size Dv50 of the core is within the above range, which can not only improve the charge exchange capacity of ions on the surface of the negative electrode active material, but also keep the side reactions on the surface of the negative electrode active material particles at a lower level, and also make the negative electrode active material have a higher gram capacity, which is conducive to the battery having high energy density, good kinetic performance and long cycle life.
[0015] In some embodiments, the volume distribution particle size Dv50 of the negative electrode active material is 8μm-25μm, and can be optionally 12μm-17μm. When the volume distribution particle size Dv50 of the negative electrode active material is within the above range, lithium ions can have good solid-phase conductivity inside the negative electrode active material particles, and the negative electrode active material can also have a smaller specific surface area, which is beneficial for the battery to have good cycle performance and kinetic performance. When the volume distribution particle size Dv50 of the negative electrode active material is within the above range, the negative electrode slurry can also have good dispersibility.
[0016] In some embodiments, the graphite is artificial graphite. The core includes artificial graphite, which can make the battery have high energy density and good cycle performance.
[0017] In some embodiments, the graphite is in a secondary particle morphology. When the graphite is in a secondary particle morphology, the isotropy of the graphite increases, which is conducive to the rapid insertion of lithium ions, thereby facilitating the battery to have good kinetic performance, and can further improve the gram capacity of the negative electrode active material and the energy density of the battery.
[0018] In some embodiments, the intensity ratio C(004) / C(110) of the diffraction peak of 004 crystal plane to the diffraction peak of 110 crystal plane of the graphite measured by X-ray diffraction method is 5.5-6.5.
[0019] In some embodiments, the gram capacity of the negative electrode active material is 354 mAh / g-361 mAh / g.
[0020] In some embodiments, the powder compaction density of the negative electrode active material under a pressure of 20000N is 1.68g / cm 3 -1.78g / cm 3 .
[0021] In some embodiments, the specific surface area of the negative electrode active material is 1.5 m 2 / g-4.5m 2 / g.
[0022] In a second aspect, the present application provides a method for preparing a negative electrode active material, comprising the following steps: providing a coke raw material; crushing, shaping and grading the coke raw material to obtain aggregate; mixing the obtained aggregate with a binder and sequentially performing granulation and graphitization to obtain graphite; solid-liquid fusion of the obtained graphite and a liquid hard carbon coating agent; carbonizing the product after the solid-liquid fusion under a protective gas atmosphere so that the liquid hard carbon coating agent is carbonized into hard carbon and coated on at least a portion of the surface of the graphite to obtain a negative electrode active material, wherein the negative electrode active material comprises a core and a coating layer located on at least a portion of the surface of the core, the core comprising graphite, and the coating layer comprising hard carbon; in the R value cumulative distribution curve of the negative electrode active material obtained under the surface scanning mode of a laser microscopic confocal Raman spectrometer, starting from the lower limit, the R value R50 with a cumulative distribution of 50% is 0.15-0.40.
[0023] In the preparation method provided in the embodiment of the present application, a liquid-phase hard carbon coating agent is used to carry out solid-liquid fusion with graphite. Since the liquid-phase hard carbon coating agent has good fluidity, it can be evenly distributed on the surface of the graphite particles, thereby improving the coating effect of the coating layer and reducing the degree of uncoating; and after the liquid-phase hard carbon coating agent is carbonized, the negative electrode active material can have a smaller R50, thereby improving the charge exchange capacity of ions on the surface of the negative electrode active material, and improving the kinetic performance of the negative electrode active material and the battery. The degree of uncoating of the negative electrode active material is reduced, and the side reactions on the surface of the negative electrode active material particles can be kept at a lower level, which is also beneficial for the battery to have good cycle performance. Therefore, the negative electrode active material prepared by the preparation method provided in the embodiment of the present application can enable the battery to have high energy density, good kinetic performance and cycle performance.
[0024] In some embodiments, the coke raw material includes one or more of petroleum-based needle coke and coal-based needle coke. These coke raw materials are anisotropic materials, which are beneficial to reduce the disorder of the core material, increase the gram capacity of the core material and the overall gram capacity of the negative electrode active material.
[0025] In some embodiments, the temperature of the graphitization treatment is 2800° C.-3800° C., and can be optionally 2850° C.-3300° C. By selecting a suitable graphitization treatment temperature, the battery can have both high energy density and good kinetic performance.
[0026] In some embodiments, the mass of the liquid phase hard carbon coating agent is 0.7%-10% of the mass of the graphite, and can be 3%-7%. The mass proportion of the liquid phase hard carbon coating agent is within the above range, which can make the degree of uncoating of the negative electrode active material within a smaller range, thereby improving the charge exchange capacity of ions on the surface of the prepared negative electrode active material, and making the side reactions on the surface of the prepared negative electrode active material particles at a lower level, and also making the prepared negative electrode active material have a higher gram capacity, which is conducive to the battery having high energy density, good kinetic performance and long cycle life.
[0027] In some embodiments, the liquid hard carbon coating agent includes a liquid resin, the viscosity of the liquid resin at 25° C. is 150 mPa·s-2000 mPa·s, and the solid content of the liquid resin is 50%-85%.
[0028] Optionally, the viscosity of the liquid resin at 25° C. is 300 mPa·s-900 mPa·s, and the solid content of the liquid resin is 60%-82%.
[0029] The viscosity of the liquid resin is within the above range, which can make the liquid resin have good fluidity and diffusibility, as well as good curing effect and coating effect. Therefore, the liquid resin can be evenly dispersed on the surface of the graphite particles, which is beneficial to improve the coating effect, reduce the degree of uncoating, and improve the coating uniformity of the surface of the graphite particles, which is beneficial to the battery to have both good dynamic performance and long cycle life.
[0030] When the solid content of the liquid resin is within the above range, the liquid resin can have good fluidity and diffusivity, as well as good curing and coating effects. Thus, the liquid resin can be evenly dispersed on the surface of the graphite particles, which is beneficial to improving the coating effect and reducing the degree of uncoating. It can also adjust the cumulative distribution of the negative electrode active material to an R value R50 of 50%, increase the disorder of the surface of the negative electrode active material particles, and enhance the charge exchange capacity of ions on the surface of the negative electrode active material, which is beneficial for the battery to have both good kinetic performance and long cycle life.
[0031] In some embodiments, the liquid resin includes at least one of liquid phenolic resin, liquid epoxy resin, liquid vinyl ester resin, liquid unsaturated polyester resin, liquid furan resin, and derivatives thereof.
[0032] In some embodiments, the liquid hard carbon coating agent includes liquid phenolic resin, and the liquid phenolic resin has a solid content of 60%-82% and a weight average molecular weight of 300-800.
[0033] Optionally, the liquid phenolic resin has a solid content of 68%-78% and a weight average molecular weight of 450-700.
[0034] Compared with other liquid resins, the hard carbon formed by carbonization and coking of liquid phenolic resin itself has better performance.
[0035] By further adjusting the solid content and weight-average molecular weight of the liquid phenolic resin within the above range, the hard carbon formed by carbonization can have better kinetic properties, and the coating effect can be improved and the degree of uncoating can be reduced, thereby enhancing the charge exchange capacity of ions on the surface of the negative electrode active material, thereby improving the kinetic properties of the negative electrode active material.
[0036] In some embodiments, the device for solid-liquid fusion of the graphite and the liquid hard carbon coating agent is a fusion machine, the stirring speed of the fusion machine is 350r / min-1000r / min, and the stirring time of solid-liquid fusion is 4min-10min. Optionally, the stirring speed of the fusion machine is 450r / min-850r / min, and the stirring time of solid-liquid fusion is 6min-8min. Increasing the stirring speed of the fusion machine is beneficial to improving the coating effect and reducing the degree of uncoating, thereby improving the charge exchange capacity of ions on the surface of the negative electrode active material, and further improving the kinetic properties of the negative electrode active material. Increasing the stirring time of solid-liquid fusion is beneficial to improving the coating effect and reducing the degree of uncoating, thereby improving the charge exchange capacity of ions on the surface of the negative electrode active material, and further improving the kinetic properties of the negative electrode active material.
[0037] In some embodiments, the carbonization treatment is carried out at a holding temperature of 900°C-1500°C.
[0038] In some embodiments, the carbonization treatment is carried out for a holding time of 2 hours to 10 hours.
[0039] In a third aspect, the present application provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises the negative electrode active material of the first aspect of the present application or the negative electrode active material prepared by the preparation method of the second aspect of the present application.
[0040] In some embodiments, the negative electrode film layer includes a first negative electrode film layer and a second negative electrode film layer located between the first negative electrode film layer and the negative electrode current collector, the thickness of the first negative electrode film layer is 30%-60% of the thickness of the negative electrode film layer, the first negative electrode film layer includes a first negative electrode active material, the second negative electrode film layer includes a second negative electrode active material, and the first negative electrode active material includes the negative electrode active material of the first aspect of the present application or the negative electrode active material prepared by the preparation method of the second aspect of the present application.
[0041] In some embodiments, the second negative electrode active material includes the negative electrode active material of the first aspect of the present application or the negative electrode active material prepared by the preparation method of the second aspect of the present application, and the mass content w1 of the first negative electrode active material in the first negative electrode film layer is greater than the mass content w2 of the second negative electrode active material in the second negative electrode film layer. This can reduce the floating problem of the negative electrode binder during the slurry drying process, reduce the negative electrode binder content on the outer surface of the negative electrode film layer, thereby facilitating the liquid phase conduction of ions inside the negative porous electrode and the charge exchange of ions on the surface of the negative electrode active material, and further improve the kinetic performance of the battery.
[0042] Optionally, a mass content w1 of the first negative electrode active material in the first negative electrode film layer is greater than or equal to 96.9%, and a mass content w2 of the second negative electrode active material in the second negative electrode film layer is less than 96.9%.
[0043] In some embodiments, the second negative electrode active material includes graphite, the graphite is in a secondary particle morphology, and a cumulative distribution of the graphite has a 50% R value R50 of 0.06-0.13.
[0044] Optionally, the mass content w1 of the first negative electrode active material in the first negative electrode film layer is greater than the mass content w2 of the second negative electrode active material in the second negative electrode film layer.
[0045] Optionally, a mass content w1 of the first negative electrode active material in the first negative electrode film layer is greater than or equal to 96.9%, and a mass content w2 of the second negative electrode active material in the second negative electrode film layer is less than 96.9%.
[0046] This can reduce the floating problem of the negative electrode binder during the slurry drying process and reduce the negative electrode binder content on the outer surface of the negative electrode film layer, which is beneficial to the liquid phase conduction of ions inside the negative electrode porous electrode and the charge exchange of ions on the surface of the negative electrode active material, thereby further improving the battery's kinetic performance.
[0047] In some embodiments, the compaction density of the negative electrode film layer is 1.62 g / cm 3 -1.80g / cm 3 , optional 1.65g / cm 3 -1.80g / cm 3 .
[0048] In some embodiments, the thickness of the negative electrode film layer is 45 μm-100 μm, and can be 70 μm-100 μm. By adjusting the thickness of the negative electrode film layer within the above range, the battery is beneficial to have better dynamic performance under the premise of high energy density.
[0049] In a fourth aspect, the present application provides a battery, comprising the negative electrode plate of the third aspect of the present application.
[0050] In a fifth aspect, the present application provides an electrical device, comprising the battery of the fourth aspect of the present application, wherein the battery is used to provide electrical energy.
[0051] The electric device of the present application includes the battery provided by the present application, and thus has at least the same advantages as the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0053] Figure 1 is a schematic diagram of a battery cell provided in some embodiments of the present application.
[0054] Figure 2 is a schematic diagram of a battery module provided in some embodiments of the present application.
[0055] Figure 3 is a schematic diagram of a battery pack provided in some embodiments of the present application.
[0056] Figure 4 yes Figure 3 An exploded diagram of the battery pack is shown.
[0057] Figure 5 It is a schematic diagram of an exploded view of a battery cell provided in some embodiments of the present application.
[0058] Figure 6 It is a schematic diagram of an electrical device provided in some embodiments of the present application.
[0059] In the drawings, the drawings are not necessarily drawn to scale.
[0060] The reference numerals are as follows: 1. battery pack; 2. upper case; 3. lower case; 4. battery module; 5. battery cell; 51. shell; 52. electrode assembly; 53. cover plate. DETAILED DESCRIPTION
[0061] Hereinafter, the negative electrode active material and its preparation method, as well as the negative electrode sheet, battery and electric device containing the same are described in detail with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0062] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0063] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0064] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0065] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0066] In the present application, the terms "plurality" and "multiple" refer to two or more.
[0067] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.
[0068] Unless otherwise specified, the values of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.
[0069] The battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may include a battery cell, a battery module or a battery pack.
[0070] A battery cell is the smallest unit of a battery, which can independently realize the functions of charging and discharging. The battery cell can be cylindrical, rectangular or in other shapes, etc., which is not limited in the embodiments of the present application. Figure 1 The battery cell 5 is a rectangular parallelepiped structure as an example.
[0071] When there are multiple battery cells, the multiple battery cells are connected in series, in parallel, or in mixed connection through a busbar. In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. In some embodiments, the battery may be a battery pack, which includes a case and battery cells, and the battery cells or battery modules are accommodated in the case. In some embodiments, the case may serve as part of the chassis structure of the vehicle. For example, part of the case may become at least a part of the floor of the vehicle, or part of the case may become at least a part of the crossbeam and longitudinal beam of the vehicle.
[0072] In some embodiments, the battery may be an energy storage device, which includes an energy storage container, an energy storage cabinet, and the like.
[0073] In some embodiments, battery cells may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module. Figure 2 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 2 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0074] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0075] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0076] Figure 3 and Figure 4 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 3 and Figure 4 As shown, the battery pack 1 may include a box body and a plurality of battery modules 4 disposed in the box body. The box body includes an upper box body 2 and a lower box body 3, and the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the box body in any manner.
[0077] The battery provided in the embodiment of the present application may include a lithium-ion battery.
[0078] The battery cell includes an electrode assembly and an electrolyte. The electrode assembly can be a winding structure or a stacked structure, which is not limited in the present application.
[0079] The battery cell may also include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte. The outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0080] In some embodiments, Figure 5 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0081] The electrode assembly generally includes a positive electrode sheet and a negative electrode sheet. The negative electrode is an electrode that absorbs or lithiates lithium ions during charging and releases or delithiates lithium during discharging. The positive electrode is an electrode that releases or delithiates lithium ions during charging and absorbs or lithiates lithium during discharging. The positive electrode sheet includes positive electrode active materials, and the negative electrode sheet includes negative electrode active materials.
[0082] When the battery is charging, the electrochemical process occurring at the negative electrode can be roughly divided into the following three steps: (1) the liquid phase conduction process of ions inside the negative electrode porous electrode, including the liquid phase diffusion process and the electrical migration process; (2) the charge exchange process of ions on the surface of the negative electrode active material; (3) the solid phase conduction process of ions inside the negative electrode active material particles.
[0083] The charge exchange ability of ions on the surface of the negative electrode active material is very important to achieve fast charging.
[0084] The commonly used negative electrode active material is graphite, but the kinetic properties of graphite are not good enough. Fast-charging hard carbon has good kinetic properties, but the energy density of the battery assembled from it is usually not high, and the cycle life of the battery is not good enough.
[0085] In view of this, an embodiment of the present application provides a negative electrode active material.
[0086] The negative electrode active material includes a core and a coating layer located on at least a portion of the surface of the core, the core includes graphite, and the coating layer includes hard carbon; in the R value cumulative distribution curve of the negative electrode active material obtained in the surface scanning mode of the laser microscopic confocal Raman spectrometer, starting from the lower limit, the R value R50 with a cumulative distribution of 50% is 0.15-0.40.
[0087] In this application, the R value of the negative electrode active material, core, and coating layer refers to the ratio of the peak heights of the D-band and G-band of its Raman spectrum, with the D-band position being 1350±50cm -1 , the G peak position is 1585±50cm -1 The R value can characterize the degree of defects and disorder of each carbon material. The larger the value, the greater the degree of defects and the higher the disorder of the carbon material.
[0088] The Raman spectra of each carbon material can be obtained by a laser micro-confocal Raman spectrometer, and the laser wavelength can be 532nm. During the test, an appropriate amount of sample can be taken to perform a full-scale scan of its surface, with a scanning area of 100μm×100μm, a step length of 2μm, and a total number of scanning points of 2500 points, thereby obtaining all R values and R value cumulative distribution curves. R50 is the R value with a cumulative distribution of 50% from the lower limit. That is, the 2500 R values obtained are arranged in order from small to large, and R50 is the R value corresponding to the 50% number arranged in order. The test instrument can be a high-precision Renishaw laser micro-confocal Raman spectrometer.
[0089] The negative electrode active material sample can be obtained by sampling during the battery preparation process, or by disassembling the sample from the prepared battery.
[0090] The core material sample can be obtained by sampling during the process of preparing the negative electrode active material.
[0091] The R value of the coating layer and the concentration of the R value refer to the properties of the hard carbon material itself formed by carbonizing the precursor compound used to prepare the coating layer material. The coating layer material sample can be obtained as follows: take an appropriate amount of the precursor compound used to prepare the coating layer material (such as the liquid hard carbon coating agent described below), and carbonize it under the same carbonization treatment conditions as those for preparing the negative electrode active material coating layer, and then grind and sieve the obtained material to obtain the coating layer material sample.
[0092] The R value of the negative electrode active material can characterize the degree of defects and disorder of the negative electrode active material. The R value R50 of the cumulative distribution of the negative electrode active material is related to the R value of the cumulative distribution of the core at 50%, the R value of the cumulative distribution of the coating layer at 50%, the thickness of the coating layer, the uniformity of the coating layer, etc. For example, when other conditions are the same, the larger the R value of the cumulative distribution of the core at 50%, the larger the R value R50 of the cumulative distribution of the negative electrode active material; the larger the thickness of the coating layer, the larger the R value R50 of the cumulative distribution of the negative electrode active material.
[0093] The cumulative distribution of the negative electrode active material is 50% of the R value R50 is 0.15-0.40, which can not only improve the charge exchange capacity of ions on the surface of the negative electrode active material, but also keep the side reactions on the surface of the negative electrode active material particles at a lower level. Therefore, the negative electrode active material provided in the embodiment of the present application can enable the battery to have high energy density, good kinetic performance and cycle performance.
[0094] The R value R50 at which the cumulative distribution of the negative electrode active material is 50% may be 0.15, 0.18, 0.20, 0.22, 0.24, 0.26, 0.28, 0.30, 0.32, 0.34, 0.36, 0.38, 0.40, or a range consisting of any of the above values.
[0095] Optionally, the R value R50 of the cumulative distribution of the negative electrode active material at 50% may be 0.20-0.35, 0.20-0.30, thereby enabling the battery to better combine high energy density, good kinetic performance and cycle performance.
[0096] By further defining the R value of the negative electrode active material, the core, and the coating layer, at least one of the energy density, kinetic performance, and cycle performance of the battery can be improved.
[0097] In some embodiments, among all R values obtained by the negative electrode active material, the number of R values R50 less than 50% of the cumulative distribution of the core may account for less than or equal to 10%.
[0098] Among all the R values obtained by the negative electrode active material, the proportion of the number of R values R50 less than 50% of the cumulative distribution of the core can more accurately represent the degree of uncoating of the negative electrode active material. The smaller the value, the smaller the degree of uncoating of the negative electrode active material, the higher the degree of isotropy of the negative electrode active material, and the more active sites of the negative electrode active material, so the charge exchange capacity of ions on the surface of the negative electrode active material is better, which can further improve the kinetic performance of the negative electrode active material and the battery; in addition, the smaller the degree of uncoating of the negative electrode active material, the less the co-embedding phenomenon of the electrolyte solvent during the cycle, which can also give the battery better cycle performance.
[0099] Optionally, among all R values obtained by the negative electrode active material, the number of R values R50 less than 50% of the cumulative distribution of the inner core may account for less than or equal to 8%, and more optionally less than or equal to 6%.
[0100] This can further improve the battery's kinetic performance and cycle performance.
[0101] In some embodiments, the R value R50 of the core of the negative electrode active material at a cumulative distribution of 50% is smaller than the R value R50 of the coating layer at a cumulative distribution of 50%.
[0102] The cumulative distribution of 50% of the R value R50 of the coating layer of the negative electrode active material is large and the disorder is large, which can make the negative electrode active material and the battery have good kinetic performance; the cumulative distribution of 50% of the R value R50 of the inner core of the negative electrode active material is small and the disorder is small, which can make the negative electrode active material as a whole have a higher gram capacity and the battery have a higher energy density.
[0103] In some embodiments, the R value R50 of the cumulative distribution of 50% of the coating layer can be 0.9-1.4, for example, it can be 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.4, or a range composed of any of the above values. Optionally, the R value R50 of the cumulative distribution of 50% of the coating layer can be 0.95-1.25. When the R value R50 of the cumulative distribution of 50% of the coating layer is within the above range, the coating layer itself has good kinetic properties, which can improve the kinetic properties of the negative electrode active material and the battery; it can also make the negative electrode active material have a smaller specific surface area, thereby reducing battery side reactions and making the battery have good cycle performance.
[0104] In some embodiments, the R value R50 at which the cumulative distribution of the kernel is 50% can be 0.06-0.13, for example, can be 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, or a range consisting of any of the above values.
[0105] The larger the R value R50 of the cumulative distribution of the core is, the better the kinetic performance of the negative electrode active material; the smaller the R value R50 of the cumulative distribution of the core is, the higher the gram capacity of the negative electrode active material. When the R value R50 of the cumulative distribution of the core is within the above range, the battery can have both high energy density and good kinetic performance.
[0106] In some embodiments, the mass of the coating layer can be 0.3%-4.5% of the mass of the core, for example, 0.3%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.4%, 2.8%, 3.2%, 3.6%, 4%, 4.5%, or the range of any of the above numerical values. Optionally, the mass of the coating layer can be 1%-3.2% of the mass of the core.
[0107] The quality of the coating layer will affect the thickness of the coating layer, and will also affect the R value R50 of 50% of the cumulative distribution of the negative electrode active material and the degree of uncoating of the coating layer.
[0108] Coating the inner core with a coating layer can reduce the contact between the inner core and the electrolyte, thereby reducing the co-embedding of the electrolyte solvent during the cycle, thereby improving the cycle performance of the battery; when the thickness of the coating layer continues to increase, the battery cycle performance will decline to a certain extent due to the large number of pores in the coating layer itself.
[0109] When the mass ratio of the coating layer is within the above range, the uncoated degree of the coating layer can be reduced, thereby improving the charge exchange capacity of ions on the surface of the negative electrode active material, and can also keep the side reactions on the surface of the negative electrode active material particles at a lower level, so that the negative electrode active material has a higher gram capacity. When the mass ratio of the coating layer is within the above range, it is beneficial for the battery to have high energy density, good kinetic performance and long cycle life.
[0110] In some embodiments, the difference between the volume distribution particle size Dv50 of the negative electrode active material and the volume distribution particle size Dv50 of the core can be 1 μm-5.5 μm, for example, 1 μm, 1.4 μm, 1.8 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4 μm, 4.2 μm, 4.5 μm, 5 μm, 5.5 μm, or a range composed of any of the above values. Optionally, the difference between the volume distribution particle size Dv50 of the negative electrode active material and the volume distribution particle size Dv50 of the core can be 1.5 μm-4.2 μm, 2 μm-4 μm.
[0111] The difference between the volume distribution particle size Dv50 of the negative electrode active material and the volume distribution particle size Dv50 of the inner core is within the above range, which can not only enhance the charge exchange capacity of ions on the surface of the negative electrode active material, but also lower the side reactions on the surface of the negative electrode active material particles, and also make the negative electrode active material have a higher gram capacity, thereby facilitating the battery to have high energy density, good kinetic performance and long cycle life.
[0112] In some embodiments, the volume distribution particle size Dv50 of the negative electrode active material may be 8 μm-25 μm, and may be optionally 12 μm-17 μm. When the volume distribution particle size Dv50 of the negative electrode active material is within the above range, lithium ions can have good solid-phase conductivity inside the negative electrode active material particles, and the negative electrode active material can also have a smaller specific surface area, which is beneficial for the battery to have both good cycle performance and kinetic performance. When the volume distribution particle size Dv50 of the negative electrode active material is within the above range, the negative electrode slurry can also have good dispersibility.
[0113] The volume distribution particle size Dv50 of the material is well known in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured using instruments and methods known in the art. For example, it can be conveniently measured using a laser particle size analyzer with reference to GB / T19077-2016 particle size distribution laser diffraction method. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0114] The graphite is artificial graphite. The inner core includes artificial graphite, which can make the battery have high energy density and good cycle performance.
[0115] In some embodiments, the graphite may be in a secondary particle morphology. When the graphite is in a secondary particle morphology, the isotropy of the graphite increases, which is beneficial for rapid lithium ion embedding, thereby facilitating the battery to have good kinetic performance, and further improving the gram capacity of the negative electrode active material and the energy density of the battery.
[0116] In some embodiments, the intensity ratio C(004) / C(110) of the diffraction peak of the 004 crystal plane to the diffraction peak of the 110 crystal plane of the graphite measured by X-ray diffraction method may be 5.5-6.5.
[0117] The intensity ratio of the diffraction peak of the 004 crystal plane and the diffraction peak of the 110 crystal plane measured by X-ray diffraction can indicate the degree of isotropy of graphite. When this value is small, the degree of isotropy of graphite is high, and graphite particles have lithium ion insertion ports in all directions, which is conducive to the rapid insertion of lithium ions, and thus helps the battery have good kinetic performance.
[0118] For example, the intensity ratio C(004) / C(110) of the 004 crystal plane diffraction peak and the 110 crystal plane diffraction peak of graphite measured by X-ray diffraction method can be tested using an X-ray diffractometer (such as Bruker D8 Discover). The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain the X-ray diffraction spectrum of the powder sample. C(004) / C(110) represents the ratio of the integral area of the 004 crystal plane diffraction peak of crystalline carbon in the powder sample to the integral area of the 110 crystal plane diffraction peak. In the X-ray diffraction analysis test, a copper target can be used as an anode target, and CuKα rays can be used as a radiation source. The wavelength of the ray is The scanning 2θ angle range was 20°-80°, and the scanning rate was 4° / min.
[0119] In some embodiments, the gram capacity of the negative electrode active material can be 354 mAh / g-361 mAh / g.
[0120] The gram capacity of the negative electrode active material can be obtained by assembling a button cell and performing a charge and discharge test. For example, the negative electrode active material sample can be mixed with the conductive agent Super P, the binder polyvinylidene fluoride (PVDF) and the solvent N-methylpyrrolidone (NMP) in a mass ratio of 91.6:1.8:6.6 to make a slurry; the prepared slurry is coated on the copper foil current collector, and then dried in an oven and cold pressed for use, and the compaction density is controlled to be 1.4g / cm 3 -1.6g / cm 3; Then, the metal lithium sheet was used as the counter electrode, the polyethylene film was used as the isolation membrane, the electrolyte was injected, and the CR2430 button cell was assembled in an argon-protected glove box. The electrolyte formula used is as follows: ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1, and then the fully dried lithium salt LiPF6 was dissolved in the mixed solvent at a ratio of 1 mol / L to prepare the electrolyte. At 25°C, the button cell was left to stand for 12 hours, then discharged to 0.005V at a constant current of 0.05C, left to stand for 10 minutes, and then discharged to 0.005V at a constant current of 50μA, left to stand for 10 minutes, and then discharged to 0.005V at a constant current of 10μA. The sum of the three discharge capacities was taken as the first cycle discharge capacity of the button cell; then, the button cell was charged to 2.0V at a constant current of 0.1C, and the first cycle charging capacity of the button cell was recorded. The ratio of the first cycle charging capacity of the button battery to the mass of the negative electrode active material sample is the gram capacity of the negative electrode active material.
[0121] In some embodiments, the compaction density of the negative electrode active material powder under a pressure of 20000N can be 1.68 g / cm 3 -1.78g / cm 3 .
[0122] For example, take an appropriate amount of negative electrode active material powder and put it in a special compaction mold, put the mold on the compaction density instrument, set different pressures, read the thickness of the powder under different pressures on the equipment (here is the thickness after pressure relief), and calculate the compaction density ρ of the negative electrode active material powder under the corresponding pressure through ρ=m / (s*h). The pressure is set to 20000N. m represents the mass of the negative electrode active material powder sample, in g. s is the bottom area of the special compaction mold, which is 1.327cm here. 2 . h is the compacted thickness of the negative electrode active material powder sample, in cm.
[0123] In some embodiments, the specific surface area of the negative electrode active material may be 1.5 m 2 / g-4.5m 2 / g.
[0124] When the specific surface area of the negative electrode active material is within the above range, the negative electrode-electrolyte interface side reactions can be reduced, the irreversible consumption of lithium ions can be reduced, and thus the cycle life of the battery can be improved.
[0125] The specific surface area of a material is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured by using the nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017 and calculated using the BET (Brunauer Emmett Teller) method, wherein the nitrogen adsorption specific surface area analysis test can be performed using the Tri-Star 3020 specific surface area pore size analysis tester from Micromeritics, USA.
[0126] The embodiment of the present application also provides a method for preparing a negative electrode active material, which can prepare the negative electrode active material provided in the embodiment of the present application.
[0127] The preparation method comprises the following steps: providing a coke raw material; crushing, shaping and grading the coke raw material to obtain aggregate; mixing the obtained aggregate with a binder and sequentially granulating and graphitizing to obtain graphite; solid-liquid fusing the obtained graphite with a liquid hard carbon coating agent; carbonizing the solid-liquid fusion product under a protective gas atmosphere so that the liquid hard carbon coating agent is carbonized into hard carbon and coated on at least part of the surface of the graphite to obtain a negative electrode active material. The negative electrode active material comprises a core and a coating layer located on at least part of the surface of the core, the core comprises graphite, and the coating layer comprises hard carbon; in the R value cumulative distribution curve obtained by the negative electrode active material in the surface scanning mode of a laser microscopic confocal Raman spectrometer, from the lower limit, the R value R50 with a cumulative distribution of 50% is 0.15-0.40.
[0128] The particle size of the coke raw material is usually relatively large, and the particle size of the coke raw material can be reduced by crushing. Optionally, the crushing process can include two steps: coarse crushing and pulverizing. Coarse crushing can crush the coke raw material into millimeter-level block particles. Pulverizing can crush the particle size of the particles from the millimeter level to tens of micrometers. After the crushing process, the surface of the coke raw material is uneven, and the shaping process can make the coke raw material particles themselves more rounded. The grading process can reduce the content of particles with too large and too small particle sizes, and can further adjust the particle size and particle size distribution of the coke raw material.
[0129] The coke raw material may include one or more of petroleum-based needle coke and coal-based needle coke. These coke raw materials are anisotropic materials, which are beneficial to reducing the disorder of the core material, increasing the gram capacity of the core material and the gram capacity of the negative electrode active material as a whole, and are also beneficial to improving the energy density of the battery.
[0130] In the preparation method provided in the embodiment of the present application, a liquid-phase hard carbon coating agent is used to carry out solid-liquid fusion with graphite. Since the liquid-phase hard carbon coating agent has good fluidity, it can be evenly distributed on the surface of the graphite particles, thereby improving the coating effect of the coating layer and reducing the degree of uncoating; and after the liquid-phase hard carbon coating agent is carbonized, the negative electrode active material can have a smaller R50, thereby improving the charge exchange capacity of ions on the surface of the negative electrode active material, and improving the kinetic performance of the negative electrode active material and the battery. The degree of uncoating of the negative electrode active material is reduced, and the side reactions on the surface of the negative electrode active material particles can be kept at a lower level, which is also beneficial for the battery to have good cycle performance. Therefore, the negative electrode active material prepared by the preparation method provided in the embodiment of the present application can enable the battery to have high energy density, good kinetic performance and cycle performance.
[0131] Optionally, the mass of the binder may be 6%-12%, and optionally 8%-10% of the mass of the aggregate obtained by the classification process, thereby enabling the graphite to have a good secondary particle morphology.
[0132] Alternatively, the binder may include asphalt.
[0133] The equipment used for the granulation process may include either a horizontal reactor or a vertical reactor.
[0134] Optionally, the granulation process can adopt a step-wise heating and heat preservation process, thereby making the graphite have good secondary particle morphology and high capacity.
[0135] Optionally, 2-4 programmed temperature rising platforms can be set during the temperature rising process.
[0136] Usually, the surface of coke raw materials from different batches and different raw materials is uneven and has many defects. Graphitization treatment can also significantly repair the surface defects of the material, thereby making the Raman value of the core material in the surface scanning mode more concentrated, and thus making the performance of the finished graphite product more consistent.
[0137] The equipment used for graphitization treatment may include any one of an Acheson graphitization furnace, a box furnace or an internal furnace.
[0138] Optionally, the temperature of the graphitization treatment may be 2800°C-3800°C, for example, 2800°C, 2850°C, 2900°C, 3000°C, 3100°C, 3200°C, 3300°C, 3400°C, 3500°C, 3600°C, 3700°C, 3800°C, or a range of any of the above values. More optionally, the temperature of the graphitization treatment may be 2850°C-3300°C. The specific time of the graphitization treatment may be reasonably selected according to the equipment used.
[0139] The graphitization temperature is high, the graphitization treatment time is long, the specific capacity of graphite is high, the disorder degree is small, and the R value R50 of the cumulative distribution of graphite is 50% small.
[0140] By selecting the appropriate graphitization treatment temperature, the battery can have both high energy density and good kinetic performance.
[0141] In some embodiments, the coking value of the liquid phase hard carbon coating agent may be 35%-50%, and optionally 38%-48%.
[0142] The coking value of a liquid hard carbon coating agent refers to the percentage of the residual carbon mass left after a quantitative liquid hard carbon coating agent sample is heated under specified conditions to the mass of the liquid hard carbon coating agent sample, and can be tested with reference to GB / T 8727-2008.
[0143] In some embodiments, the mass of the liquid-phase hard carbon coating agent can be 0.7%-10% of the mass of the graphite, for example, 0.7%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a range of any of the above values. Alternatively, the mass of the liquid-phase hard carbon coating agent can be 3%-7% of the mass of the graphite.
[0144] As the mass proportion of the liquid hard carbon coating agent increases, the R value R50 of 50% of the cumulative distribution of the negative electrode active material increases, and the disorder degree of the surface of the negative electrode active material particles increases.
[0145] The mass proportion of the liquid phase hard carbon coating agent is within the above range, which can make the uncoated degree of the negative electrode active material within a smaller range, thereby not only improving the charge exchange capacity of ions on the surface of the prepared negative electrode active material, but also making the side reactions on the surface of the prepared negative electrode active material particles at a lower level, and also making the prepared negative electrode active material have a higher gram capacity, which is beneficial for the battery to have high energy density, good kinetic performance and long cycle life.
[0146] In some embodiments, the liquid phase hard carbon coating agent includes a liquid resin, and the liquid resin is a hard carbon precursor material. When the coating layer includes hard carbon, the negative electrode active material and the battery can have better kinetic performance.
[0147] The liquid resin can be purchased from the market, or synthesized according to methods known in the art, or can be obtained by mixing and stirring the resin powder with a solvent.
[0148] In some embodiments, the viscosity of the liquid resin at 25° C. may be 150 mPa·s-2000 mPa·s, for example, 150 mPa·s, 200 mPa·s, 300 mPa·s, 400 mPa·s, 500 mPa·s, 600 mPa·s, 700 mPa·s, 800 mPa·s, 900 mPa·s, 1050 mPa·s, 1200 mPa·s, 1400 mPa·s, 1600 mPa·s, 1800 mPa·s, 2000 mPa·s, or a range consisting of any of the above values. Optionally, the viscosity of the liquid resin at 25° C. may be 300 mPa·s-900 mPa·s.
[0149] The viscosity of the liquid resin can be tested with reference to GB / T 14074-2017. The test temperature is 25°C and the test equipment can be a NDJ-1 type rotational viscometer.
[0150] The viscosity of the liquid resin is within the above range, which can make the liquid resin have good fluidity and diffusibility, as well as good curing effect and coating effect. Therefore, the liquid resin can be evenly dispersed on the surface of the graphite particles, which is beneficial to improve the coating effect, reduce the degree of uncoating, and improve the coating uniformity of the surface of the graphite particles, which is beneficial to the battery to have both good dynamic performance and long cycle life.
[0151] In some embodiments, the solid content of the liquid resin may be 50%-85%, and optionally 60%-82%.
[0152] The solid content of the liquid phase hard carbon coating agent can be tested by the drying method in accordance with GB / T 14074-2017. The free components and water in the liquid phase hard carbon coating agent will volatilize at high temperatures. The solid content of the liquid phase hard carbon coating agent refers to the percentage of the remaining mass to the total mass after drying under specified conditions. The oven temperature is set to 150°C and baked to constant weight.
[0153] When the solid content of the liquid resin is within the above range, the liquid resin can have good fluidity and diffusivity, as well as good curing and coating effects. Thus, the liquid resin can be evenly dispersed on the surface of the graphite particles, which is beneficial to improving the coating effect and reducing the degree of uncoating. It can also adjust the cumulative distribution of the negative electrode active material to an R value R50 of 50%, increase the disorder of the surface of the negative electrode active material particles, and enhance the charge exchange capacity of ions on the surface of the negative electrode active material, which is beneficial for the battery to have both good kinetic performance and long cycle life.
[0154] In some embodiments, the liquid resin may include at least one of liquid phenolic resin, liquid epoxy resin, liquid vinyl ester resin, liquid unsaturated polyester resin, liquid furan resin, and their respective derivatives. Derivatives generally refer to products derived from the substitution of hydrogen atoms or atomic groups in a polymer by other atoms or atomic groups.
[0155] The liquid resin is a good hard carbon precursor material. As a liquid phase hard carbon coating agent, it can better improve the dynamic performance of the battery and also make the battery have good cycle performance.
[0156] In some embodiments, the liquid hard carbon coating agent includes liquid phenolic resin. The solid content of the liquid phenolic resin may be 60%-82% and the weight average molecular weight may be 300-800.
[0157] Optionally, the solid content of the liquid phenolic resin may be 68%-78% and the weight average molecular weight may be 450-700.
[0158] Compared with other liquid resins, the hard carbon formed by carbonization and coking of liquid phenolic resin itself has better performance.
[0159] By further adjusting the solid content and weight-average molecular weight of the liquid phenolic resin within the above range, the hard carbon formed by carbonization can have better kinetic properties, and the coating effect can be improved and the degree of uncoating can be reduced, thereby enhancing the charge exchange capacity of ions on the surface of the negative electrode active material, thereby improving the kinetic properties of the negative electrode active material.
[0160] The weight average molecular weight of the liquid phase hard carbon coating agent can be tested by gel permeation chromatography. The testing instrument can be an Agilent 1290 Infinity II GPC system. The eluent can be tetrahydrofuran, and polystyrene standards are used for calibration.
[0161] The liquid phenolic resin can be a phenolic compound, an aldehyde compound, etc., which is formed by condensation in the presence of an alkaline catalyst. The condensation reaction begins to generate a liquid. The liquid phenolic resin mentioned in the embodiment of the present application is a resol phenolic resin.
[0162] The phenolic compound may include one or more of phenol, cresol, dimethylphenol, nonylphenol, bisphenol A, bisphenol F, resorcinol, propylphenol, ethylphenol, and cardanol, and phenol may be selected. The aldehyde compound may include one or more of formaldehyde, acetaldehyde, butyraldehyde, paraformaldehyde, and furfural, and formaldehyde may be selected. The alkali catalyst may include one or more of sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, magnesium hydroxide, ammonia, sodium carbonate, and tertiary amine.
[0163] In some embodiments, the device for solid-liquid fusion of graphite and liquid hard carbon coating agent may be a fusion machine.
[0164] Optionally, the stirring speed of the fusion machine can be 350r / min-1000r / min, for example, 350r / min, 400r / min, 450r / min, 500r / min, 550r / min, 600r / min, 650r / min, 700r / min, 750r / min, 800r / min, 850r / min, 900r / min, 1000r / min, or a range composed of any of the above values. More optionally, the stirring speed of the fusion machine can be 450r / min-850r / min.
[0165] Increasing the stirring speed of the fusion machine is beneficial to improving the coating effect and reducing the degree of uncoating, thereby improving the charge exchange capacity of ions on the surface of the negative electrode active material, and further improving the kinetic performance of the negative electrode active material; however, excessive stirring speed of the fusion machine will destroy the outer surface structure of the inner core, and strong centrifugation will also cause mass loss of the liquid hard carbon coating agent.
[0166] Optionally, the stirring time of solid-liquid fusion can be 4 min-10 min, for example, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, or a range of any of the above values. More optionally, the stirring time of solid-liquid fusion can be 6 min-8 min.
[0167] Increasing the stirring time of solid-liquid fusion is beneficial to improving the coating effect and reducing the degree of uncoating, thereby improving the charge exchange capacity of ions on the surface of the negative electrode active material, and further improving the kinetic performance of the negative electrode active material. However, if the stirring time is too long, the improvement in the coating effect is not obvious, and energy consumption will also increase.
[0168] In some embodiments, the carbonization process equipment may be a track kiln.
[0169] In some embodiments, the holding temperature of the carbonization treatment may be 900° C.-1500° C., for example, 900° C., 1000° C., 1050° C., 1100° C., 1150° C., 1200° C., 1250° C., 1300° C., 1350° C., 1400° C., 1500° C., or a range of any of the above values. Optionally, the holding temperature of the carbonization treatment may be 1050° C.-1350° C.
[0170] In some embodiments, the holding time of the carbonization treatment can be 2h-10h, for example, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or a range of any of the above values. Optionally, the holding time of the carbonization treatment can be 5h-8h. The holding time of the carbonization treatment refers to the residence time at the holding temperature.
[0171] In some embodiments, the preparation method may further include the steps of: depolymerizing, screening and demagnetizing the carbonized material.
[0172] Depolymerization can be carried out in a depolymerizer. Depolymerization can eliminate the weak adhesion of the coating surface and reduce the problem of excessive agglomeration of the finished product particles. Screening can reduce the content of large particles and fine powder in the finished product, which is conducive to obtaining the desired particle size and particle size distribution. Demagnetization can reduce the content of magnetic impurities in the finished product. Magnetic impurities will increase the self-discharge of the battery and reduce the battery performance.
[0173] [Negative electrode]
[0174] The battery cell includes a negative electrode plate.
[0175] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0176] In some embodiments, the negative electrode current collector may include a metal foil, a three-dimensional porous current collector, or a composite current collector. As an example of a metal foil, copper foil, copper alloy foil, nickel foil, nickel alloy foil, aluminum foil, and aluminum alloy foil may be used. As an example of a three-dimensional porous current collector, copper mesh, nickel mesh, foam copper, foam nickel, and foam aluminum may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, aluminum, aluminum alloy, silver, and silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0177] The negative electrode film layer includes the negative electrode active material or the negative electrode active material prepared by the preparation method, thereby enabling the battery to have high energy density, good kinetic performance and cycle performance.
[0178] In some embodiments, the negative electrode film layer may also include other negative electrode active materials known in the art, for example, other negative electrode active materials include but are not limited to one or more of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate.
[0179] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. As an example, the negative electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0180] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. As an example, the negative electrode binder may include, butadiene styrene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS) or more.
[0181] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include but are not limited to thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like.
[0182] In some embodiments, the thickness of the negative electrode film layer may be 45 μm-100 μm, optionally 55 μm-100 μm, 70 μm-100 μm. The thickness of the negative electrode film layer is the thickness of the negative electrode film layer on one side of the negative electrode current collector. The thickness of the negative electrode film layer can be measured with a micrometer.
[0183] The thickness of the negative electrode film layer is related to the ion embedding speed and the polarization size of the negative electrode, so its thickness will affect the dynamic performance of the negative electrode sheet. Generally, the thicker the negative electrode film layer, the more difficult it is for ions to diffuse in the liquid phase inside the negative electrode porous electrode under the same conditions.
[0184] By adjusting the thickness of the negative electrode film layer within the above range, the battery can have better dynamic performance while having high energy density.
[0185] In some embodiments, the negative electrode film layer includes a first negative electrode film layer and a second negative electrode film layer located between the first negative electrode film layer and the negative electrode current collector, the thickness of the first negative electrode film layer is 30%-60% of the thickness of the negative electrode film layer, and the thickness of the second negative electrode film layer is 70%-40% of the thickness of the negative electrode film layer. Optionally, the thickness of the first negative electrode film layer is 30%-40% of the thickness of the negative electrode film layer, and the thickness of the second negative electrode film layer is 70%-60% of the thickness of the negative electrode film layer.
[0186] The first negative electrode film layer includes a first negative electrode active material, the second negative electrode film layer includes a second negative electrode active material, and the first negative electrode active material includes the above negative electrode active material or the negative electrode active material prepared by the above preparation method. Thus, the battery can have high energy density, good kinetic performance and cycle performance.
[0187] Optionally, in some embodiments, the second negative electrode active material may include the above-mentioned negative electrode active material or the negative electrode active material prepared by the above-mentioned preparation method, the mass content w1 of the first negative electrode active material in the first negative electrode film layer is greater than the mass content w2 of the second negative electrode active material in the second negative electrode film layer, and the mass content of the negative electrode binder in the first negative electrode film layer is less than the mass content of the negative electrode binder in the second negative electrode film layer.
[0188] During the slurry drying process, the negative electrode binder will float up, causing the negative electrode binder content on the outer surface of the negative electrode film layer to increase, which is not conducive to the liquid phase conduction of ions inside the negative electrode porous electrode and the charge exchange of ions on the surface of the negative electrode active material.
[0189] By partitioning the negative electrode film layer and making the mass content w1 of the first negative electrode active material in the first negative electrode film layer greater than the mass content w2 of the second negative electrode active material in the second negative electrode film layer, and the mass content of the negative electrode binder in the first negative electrode film layer is less than the mass content of the negative electrode binder in the second negative electrode film layer, the floating problem of the negative electrode binder during the slurry drying process can be reduced, and the negative electrode binder content on the outer surface of the negative electrode film layer can be reduced, which is beneficial to the liquid phase conduction of ions inside the negative porous electrode and the charge exchange of ions on the surface of the negative electrode active material, thereby further improving the battery's kinetic performance.
[0190] Optionally, the mass content w1 of the second negative electrode active material in the first negative electrode film layer may be greater than or equal to 96.9%, and may be 96.9%-97.4%.
[0191] Optionally, the mass content w2 of the second negative electrode active material in the second negative electrode film layer may be less than 96.9%, and may be 96.4%-96.8%.
[0192] In some alternative embodiments, the second negative electrode active material may include graphite, the graphite is a secondary particle morphology, and the cumulative distribution of the graphite is 50% R value R50 is 0.06-0.13. The second negative electrode active material can be the core of the negative electrode active material provided in the above embodiment of the present application, that is, graphite. The second negative electrode active material does not have a coating layer, thereby enabling the battery to have a higher energy density.
[0193] Optionally, the mass content w1 of the first negative electrode active material in the first negative electrode film layer is greater than the mass content w2 of the second negative electrode active material in the second negative electrode film layer, and the mass content of the negative electrode binder in the first negative electrode film layer is less than the mass content of the negative electrode binder in the second negative electrode film layer.
[0194] By partitioning the negative electrode film layer and making the mass content w1 of the first negative electrode active material in the first negative electrode film layer greater than the mass content w2 of the second negative electrode active material in the second negative electrode film layer, and the mass content of the negative electrode binder in the first negative electrode film layer is less than the mass content of the negative electrode binder in the second negative electrode film layer, the floating problem of the negative electrode binder during the slurry drying process can be reduced, and the negative electrode binder content on the outer surface of the negative electrode film layer can be reduced, which is beneficial to the liquid phase conduction of ions inside the negative porous electrode and the charge exchange of ions on the surface of the negative electrode active material, thereby further improving the battery's kinetic performance.
[0195] Optionally, the mass content w1 of the second negative electrode active material in the first negative electrode film layer may be greater than or equal to 96.9%, and may be 96.9%-97.4%.
[0196] Optionally, the mass content w2 of the second negative electrode active material in the second negative electrode film layer may be less than 96.9%, and may be 96.4%-96.8%.
[0197] In some embodiments, the compaction density of the negative electrode film layer can be 1.62 g / cm 3 -1.80g / cm 3 , optional 1.65g / cm 3 -1.80g / cm 3 The negative electrode active material provided in the embodiment of the present application or the negative electrode active material prepared by the preparation method provided in the embodiment of the present application can make the negative electrode film layer have a high compaction density.
[0198] The compaction density of the negative electrode film layer refers to the ratio of the surface density of the negative electrode film layer to the thickness of the negative electrode film layer. The surface density of the negative electrode film layer refers to the ratio of the weight of the negative electrode film layer after coating, drying and rolling to the coating area.
[0199] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, negative electrode conductive agent, negative electrode binder, other optional additives, etc. in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0200] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode plate may also include a protective layer covering the surface of the negative electrode film layer.
[0201] [Positive electrode]
[0202] The battery cell includes a positive electrode plate.
[0203] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0204] The positive electrode film layer includes a positive electrode active material. For example, the positive electrode active material may include, but is not limited to, one or more of lithium transition metal oxides, lithium-containing phosphates, and their respective modified compounds.
[0205] As an example, the lithium transition metal oxide may include, but is not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. In some embodiments, the lithium transition metal oxide may include Li a Ni b Co c M d O e A f , wherein 0<a≤1.2; 0.8≤b<1; 0<c<1; 0<d<1; 1≤e≤2; 0≤f≤1; M includes but is not limited to one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B; A includes but is not limited to one or more of N, F, S and Cl. This can further improve the energy density of the battery cell. Optionally, the lithium transition metal oxide may include but is not limited to LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.80 Co 0.15 Al 0.05 O2、LiNi 0.9 Co 0.06 Mn 0.04 O2、LiNi 0.92 Co 0.06 Mn 0.02 O2、LiNi 0.96 Co 0.02 Mn 0.02 One or more of O2.
[0206] The charging and discharging process of the battery cell is accompanied by the deintercalation and consumption of Li, and the molar content of Li in the battery cell is different when it is discharged to different states. In the examples of the present application regarding the positive electrode active materials, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is applied to the battery cell, and after the charge and discharge cycle, the molar content of Li may change.
[0207] In the examples of the present application regarding the positive electrode active materials, the molar content of O is only a theoretical value. Oxygen release from the lattice will cause the molar content of O to change, and the actual molar content of O will fluctuate.
[0208] As an example, the lithium-containing phosphate may include, but is not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.
[0209] The modified compounds of the above-mentioned positive electrode active materials may be the ones that undergo doping modification and / or surface coating modification on the positive electrode active materials.
[0210] In some embodiments, the positive electrode film layer may also optionally include a positive electrode conductive agent. As an example, the positive electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0211] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. As an example, the positive electrode binder may include, but is not limited to, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylic resin, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS) One or more.
[0212] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0213] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, positive electrode conductive agent, positive electrode binder and any other components in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.
[0214] [Electrolytes]
[0215] The battery cell includes an electrolyte. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can include one or more of a solid electrolyte and a liquid electrolyte (ie, an electrolyte).
[0216] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0217] In some embodiments, as an example, the electrolyte salt may include, but is not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP).
[0218] In some embodiments, the solvent may include, but is not limited to, one or more of an ester solvent, a sulfone solvent, and an ether solvent. As an example, the solvent may include, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), and one or more of diethyl sulfone (ESE).
[0219] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature power performance.
[0220] [Isolation film]
[0221] Battery cells using electrolytes and some battery cells using solid electrolytes also include a separator, which is disposed between the positive electrode sheet and the negative electrode sheet and mainly serves to prevent internal short circuits.
[0222] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.
[0223] In some embodiments, the material of the isolation membrane may include, but is not limited to, one or more of glass fiber, non-woven fabric, polyethylene (PE), polypropylene (PP) and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.
[0224] The preparation method of battery cells is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the above-mentioned electrolyte is injected after drying. After packaging, standing, formation and other processes, a battery cell is obtained. Multiple battery cells can also be further connected in series, in parallel or in mixed connection to form a battery module. Multiple battery modules can also be connected in series, in parallel or in mixed connection to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.
[0225] Electrical devices
[0226] The embodiment of the present application also provides an electrical device, which includes a battery provided in the embodiment of the present application, and the battery is used to provide electrical energy. The battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0227] The electrical device can select a specific type of battery, such as a battery cell, a battery module or a battery pack, according to its usage requirements.
[0228] Figure 6 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.
[0229] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.
[0230] Example
[0231] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations can be made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.
[0232] Example 1
[0233] (1) Preparation of negative electrode active materials
[0234] The petroleum needle coke is crushed, shaped and graded to obtain aggregate; the obtained aggregate is mixed with binder asphalt in a mass ratio of 100:8 and placed in a horizontal reactor for heating and granulation. A step-by-step heating and insulation process is adopted during heating. The program temperature platforms are set to 200°C, 300°C, and 600°C, respectively. The temperature is kept constant at 200°C for 1h, 300°C for 2h, and 600°C for 2h, and then taken out of the furnace after cooling for 3h; the granulated material is placed in an Acheson graphitization furnace for graphitization at 3000°C for about 50h to obtain graphite.
[0235] A fusion machine is used to fuse graphite and a liquid hard carbon coating agent in a mass ratio of 100:5. The stirring speed of the fusion machine is 600 r / min, the stirring time is 7 min, and the liquid hard carbon coating agent is a commercially available liquid phenolic resin with a weight average molecular weight of 580, a viscosity of 550 mPa·s at 25°C, and a solid content of 70%-71%. The product after solid-liquid fusion is placed in a track kiln, heated to 1150°C for carbonization treatment under a nitrogen atmosphere, and the heat preservation time is 6 hours. Then the product is cooled to 50°C and taken out of the kiln. After depolymerization, screening and demagnetization treatment, a negative electrode active material is obtained.
[0236] (2) Preparation of negative electrode sheet
[0237] The negative electrode active material, thickener sodium carboxymethyl cellulose, negative electrode binder styrene-butadiene rubber (SBR), and negative electrode conductive agent Super P were mixed in a mass ratio of 97.3:1.1:0.8:0.8, and deionized water was added as a solvent. The mixture was stirred evenly under the action of a vacuum mixer to prepare a first negative electrode slurry.
[0238] The negative electrode active material, thickener sodium carboxymethyl cellulose, negative electrode binder styrene butadiene rubber (SBR), and negative electrode conductive agent Super P were mixed in a mass ratio of 96.5:1.1:2.0:0.4, deionized water solvent was added, and the mixture was stirred evenly under the action of a vacuum mixer to prepare a second negative electrode slurry.
[0239] The second negative electrode slurry was evenly coated on both surfaces of the negative electrode current collector copper foil, the first negative electrode slurry was coated on the second negative electrode slurry, the negative electrode current collector coated with the slurry was dried at room temperature and then transferred to an oven for drying, and then cold pressed and cut to obtain a negative electrode sheet. The thickness of the negative electrode film layer on one side of the negative electrode current collector was 58 μm. The ratio of the coating thickness of the first negative electrode slurry to the coating thickness of the second negative electrode slurry was 4:6.
[0240] (3) Preparation of positive electrode sheet
[0241] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, positive electrode conductive agent Super P, and positive electrode binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:2:2, and solvent N-methylpyrrolidone (NMP) is added, and stirred under the action of a vacuum mixer until the system becomes uniform and transparent to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on both surfaces of the positive electrode collector aluminum foil; the positive electrode collector coated with the slurry is dried at room temperature and then transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0242] (4) Preparation of electrolyte
[0243] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then fully dried lithium salt LiPF6 is dissolved in the mixed solvent at a ratio of 1 mol / L to prepare an electrolyte.
[0244] (5) Preparation of isolation membrane
[0245] Choose 12 micron polyethylene film.
[0246] (6) Preparation of batteries (full batteries)
[0247] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the prepared electrolyte is injected into the dried electrode assembly, and a battery is obtained after vacuum packaging, standing, forming, shaping and other processes.
[0248] Comparative Example 1
[0249] The preparation process of the battery is the same as that of Example 1 except that the preparation process of the negative electrode active material is different.
[0250] (1) Preparation of negative electrode active materials
[0251] The petroleum needle coke is crushed, shaped and graded to obtain aggregate; the obtained aggregate is mixed with binder asphalt in a mass ratio of 100:8 and placed in a horizontal reactor for heating and granulation. A step-by-step heating and insulation process is adopted during heating. The program temperature platforms are set to 200°C, 300°C, and 600°C, respectively. The temperature is kept constant at 200°C for 1h, 300°C for 2h, and 600°C for 2h, and then taken out of the furnace after cooling for 3h; the granulated material is placed in an Acheson graphitization furnace for graphitization at 3000°C for about 50h, and then sieving and demagnetization are performed to obtain a negative electrode active material.
[0252] Comparative Example 2
[0253] The preparation process of the battery is the same as that of Example 1 except that the preparation process of the negative electrode active material is different.
[0254] (1) Preparation of negative electrode active materials
[0255] The petroleum needle coke is crushed, shaped and graded to obtain aggregate; the obtained aggregate is mixed with binder asphalt in a mass ratio of 100:8 and placed in a horizontal reactor for heating and granulation. A step-by-step heating and insulation process is adopted during heating. The program temperature platforms are set to 200°C, 300°C, and 600°C, respectively. The temperature is kept constant at 200°C for 1h, 300°C for 2h, and 600°C for 2h. The material is taken out of the furnace after cooling for 3h. The granulated material is placed in an Acheson graphitization furnace for graphitization at 2850°C for 45h to obtain graphite.
[0256] A VC mixer is used to mix graphite and a solid-phase coating agent in a mass ratio of 100:5. The solid-phase coating agent is asphalt with a softening point of 270°C. The solid-solid mixing product is placed in a track kiln and heated to 1150°C for carbonization treatment under a nitrogen atmosphere for 6 hours. The kiln is then cooled to 50°C and taken out of the kiln. After depolymerization, screening and demagnetization treatment, the negative electrode active material is obtained.
[0257] Performance test of liquid hard carbon coating agent
[0258] The viscosity of the liquid hard carbon coating agent was tested with reference to GB / T 14074-2017. The test temperature was 25°C and the test equipment was NDJ-1 type rotational viscometer.
[0259] The solid content of the liquid hard carbon coating agent was tested by drying method according to GB / T 14074-2017. The oven temperature was set at 150°C and baked to constant weight.
[0260] Test Section
[0261] (1) Raman spectroscopy test of negative electrode active materials
[0262] The test instrument is a high-precision Renishaw laser microscope confocal Raman spectrometer with a laser wavelength of 532nm.
[0263] During the test, take an appropriate amount of negative electrode active material sample and scan its surface in all directions. The scanning area is 100μm×100μm, the step length is 2μm, and the total number of scanning points is 2500 points. The R value and R value cumulative distribution curve at different positions are obtained. The R value refers to the ratio of the peak height of the D peak and the G peak of the Raman spectrum. The D peak position is 1350±50cm -1 , the G peak position is 1585±50cm -1 R50 is the R value at which the cumulative distribution from the lower limit is 50%.
[0264] The Raman spectrum test of graphite and coating material is carried out in a similar manner as described above. The coating material sample can be obtained in the following manner: take an appropriate amount of liquid hard carbon coating agent or solid coating agent, and perform carbonization treatment according to the same carbonization treatment conditions as in each embodiment and comparative example, and then grind and sieve the obtained material to obtain the coating material sample.
[0265] Among all the R values of the obtained negative electrode active material, the percentage of the R value R50 less than 50% of the cumulative distribution of graphite is marked as the uncoated degree X of the negative electrode active material.
[0266] (2) Battery mass energy density test
[0267] At 25°C, the batteries prepared in the embodiments and comparative examples were fully charged at a rate of 0.33C and fully discharged at a rate of 0.33C. After three times of charge and discharge, the actual discharge energy D0 of the battery was recorded. The battery charge and discharge voltage range was 2.5V to 4.25V. At 25°C, the battery was weighed using an electronic balance. The ratio of the actual discharge energy D0 of the battery to the mass of the battery is the mass energy density of the battery.
[0268] (3) Battery cycle performance test
[0269] At 35°C, the batteries prepared in the embodiments and comparative examples were fully charged at a rate of 1C and fully discharged at a rate of 0.5C, and the charge and discharge cycles were repeated, and the charge and discharge voltage range of the battery was 2.5V to 4.25V. The capacity retention rate of the battery after 2000 cycles is used to characterize the cycle performance of the battery. The higher the value, the better the cycle performance of the battery. The capacity retention rate of the battery after 2000 cycles = the discharge capacity after 2000 cycles / the discharge capacity after the first cycle.
[0270] (4) Battery critical charge rate test
[0271] At 25°C, the batteries prepared in the embodiments and comparative examples were charged and discharged at an equivalent charge rate of xC, fully charged, and 1C fully discharged. After 10 cycles, the batteries were fully charged at an equivalent charge rate of xC, the negative electrode plates were disassembled, and the lithium deposition on the surface was observed. The battery charge and discharge voltage range is 2.5V to 4.25V. If lithium is not deposited on the negative electrode surface, the equivalent charge rate xC is increased by 0.1C as a gradient to perform the above test until lithium is deposited on the negative electrode surface. The test is stopped, the charge rate xC at this time is recorded, and (x-0.1)C is recorded as the critical charge rate of the battery.
[0272] Table 1
[0273]
[0274] It can be seen from the test results of Example 1 and Comparative Example 1 that by providing a coating layer on the graphite surface and making the cumulative distribution of the coated negative electrode active material 50% R value R50 greater than 0.15, the battery can have a higher critical charging rate, thereby making the battery have better fast charging performance.
[0275] Table 2
[0276]
[0277] It can be seen from the test results in Table 2 that compared with the negative electrode active material prepared by the solid phase coating agent in Comparative Example 2, the liquid phase hard carbon coating agent used in Example 1 can reduce the R value R50 of the cumulative distribution of the negative electrode active material to 50%, thereby enabling the battery to have better fast charging performance while also having a higher cycle capacity retention rate.
[0278] It can also be seen from the test results in Table 2 that, compared with the negative electrode active material prepared by using a solid phase coating agent in Comparative Example 2, the use of a liquid phase hard carbon coating agent in Example 1 can also make the battery have a higher energy density.
[0279] Example 2
[0280] The preparation process of the battery is the same as that of Example 1 except that the preparation process of the negative electrode active material is different.
[0281] (1) Preparation of negative electrode active materials
[0282] The petroleum needle coke is crushed, shaped and graded to obtain aggregate; the obtained aggregate is mixed with binder asphalt in a mass ratio of 100:8 and placed in a horizontal reactor for heating and granulation. A step-by-step heating and insulation process is adopted during heating. The program temperature platforms are set to 200°C, 300°C, and 600°C, respectively. The temperature is kept constant at 200°C for 1h, 300°C for 2h, and 600°C for 2h. The material is taken out of the furnace after cooling for 3h. The granulated material is placed in an Acheson graphitization furnace for graphitization at 3200°C for about 55h to obtain graphite.
[0283] A fusion machine is used to fuse graphite and a liquid hard carbon coating agent in a mass ratio of 100:5. The stirring speed of the fusion machine is 600 r / min, the stirring time is 7 min, and the liquid hard carbon coating agent is a commercially available liquid phenolic resin with a weight average molecular weight of 580, a viscosity of 550 mPa·s at 25°C, and a solid content of 70%-71%. The product after solid-liquid fusion is placed in a track kiln, heated to 1150°C for carbonization treatment under a nitrogen atmosphere, and the heat preservation time is 6 hours. Then the product is cooled to 50°C and taken out of the kiln. After depolymerization, screening and demagnetization treatment, a negative electrode active material is obtained.
[0284] Example 3
[0285] The preparation process of the battery is the same as that of Example 1 except that the preparation process of the negative electrode active material is different.
[0286] (1) Preparation of negative electrode active materials
[0287] The petroleum needle coke is crushed, shaped and graded to obtain aggregate; the obtained aggregate is mixed with binder asphalt in a mass ratio of 100:8 and placed in a horizontal reactor for heating and granulation. A step-by-step heating and insulation process is adopted during heating. The program temperature platforms are set to 200°C, 300°C, and 600°C, respectively. The temperature is kept constant at 200°C for 1 hour, 300°C for 2 hours, and 600°C for 2 hours. The material is taken out of the furnace after cooling for 3 hours. The granulated material is placed in an Acheson graphitization furnace for graphitization at 2850°C for about 45 hours to obtain graphite.
[0288] A fusion machine is used to fuse graphite and a liquid hard carbon coating agent in a mass ratio of 100:5. The stirring speed of the fusion machine is 600 r / min, the stirring time is 7 min, and the liquid hard carbon coating agent is a commercially available liquid phenolic resin with a weight average molecular weight of 580, a viscosity of 550 mPa·s at 25°C, and a solid content of 70%-71%. The product after solid-liquid fusion is placed in a track kiln, heated to 1150°C for carbonization treatment under a nitrogen atmosphere, and the heat preservation time is 6 hours. Then the product is cooled to 50°C and taken out of the kiln. After depolymerization, screening and demagnetization treatment, a negative electrode active material is obtained.
[0289] Table 3
[0290]
[0291] It can be seen from the test results in Table 3 that, under the same conditions, by adjusting the preparation process of the core graphite, the cumulative distribution of the negative electrode active material can be adjusted to an R value R50 of 50%.
[0292] It can also be seen from the test results in Table 3 that, when the negative electrode active material is not coated to the same extent, the R value R50 at which the cumulative distribution of the negative electrode active material is 50% increases, and the fast charging performance of the battery is improved.
[0293] Example 4
[0294] The preparation process of the battery is the same as that of Example 1 except that the preparation process of the negative electrode active material is different.
[0295] (1) Preparation of negative electrode active materials
[0296] The petroleum needle coke is crushed, shaped and graded to obtain aggregate; the obtained aggregate is mixed with binder asphalt in a mass ratio of 100:8 and placed in a horizontal reactor for heating and granulation. A step-by-step heating and insulation process is adopted during heating. The program temperature platforms are set to 200°C, 300°C, and 600°C, respectively. The temperature is kept constant at 200°C for 1h, 300°C for 2h, and 600°C for 2h, and then taken out of the furnace after cooling for 3h; the granulated material is placed in an Acheson graphitization furnace for graphitization at 3000°C for about 50h to obtain graphite.
[0297] A fusion machine is used to fuse graphite and a liquid hard carbon coating agent in a mass ratio of 100:3. The stirring speed of the fusion machine is 600 r / min, the stirring time is 7 min, and the liquid hard carbon coating agent is a commercially available liquid phenolic resin with a weight average molecular weight of 580, a viscosity of 550 mPa·s at 25°C, and a solid content of 70%-71%. The product after solid-liquid fusion is placed in a track kiln, heated to 1150°C for carbonization treatment under a nitrogen atmosphere, and the heat preservation time is 6 hours. Then the product is cooled to 50°C and taken out of the kiln. After depolymerization, screening and demagnetization treatment, a negative electrode active material is obtained.
[0298] Example 5
[0299] The preparation process of the battery is the same as that of Example 1 except that the preparation process of the negative electrode active material is different.
[0300] (1) Preparation of negative electrode active materials
[0301] The petroleum needle coke is crushed, shaped and graded to obtain aggregate; the obtained aggregate is mixed with binder asphalt in a mass ratio of 100:8 and placed in a horizontal reactor for heating and granulation. A step-by-step heating and insulation process is adopted during heating. The program temperature platforms are set to 200°C, 300°C, and 600°C, respectively. The temperature is kept constant at 200°C for 1h, 300°C for 2h, and 600°C for 2h, and then taken out of the furnace after cooling for 3h; the granulated material is placed in an Acheson graphitization furnace for graphitization at 3000°C for about 50h to obtain graphite.
[0302] A fusion machine is used to fuse graphite and a liquid hard carbon coating agent in a mass ratio of 100:7. The stirring speed of the fusion machine is 600 r / min, the stirring time is 7 min, and the liquid hard carbon coating agent is a commercially available liquid phenolic resin with a weight average molecular weight of 580, a viscosity of 550 mPa·s at 25°C, and a solid content of 70%-71%. The product after solid-liquid fusion is placed in a track kiln, heated to 1150°C for carbonization treatment under a nitrogen atmosphere, and the heat preservation time is 6 hours. Then the product is cooled to 50°C and taken out of the kiln. After depolymerization, screening and demagnetization treatment, a negative electrode active material is obtained.
[0303] Example 6
[0304] The preparation process of the battery is the same as that of Example 1 except that the preparation process of the negative electrode active material is different.
[0305] (1) Preparation of negative electrode active materials
[0306] The petroleum needle coke is crushed, shaped and graded to obtain aggregate; the obtained aggregate is mixed with binder asphalt in a mass ratio of 100:8 and placed in a horizontal reactor for heating and granulation. A step-by-step heating and insulation process is adopted during heating. The program temperature platforms are set to 200°C, 300°C, and 600°C, respectively. The temperature is kept constant at 200°C for 1h, 300°C for 2h, and 600°C for 2h, and then taken out of the furnace after cooling for 3h; the granulated material is placed in an Acheson graphitization furnace for graphitization at 3000°C for about 50h to obtain graphite.
[0307] A fusion machine is used to fuse graphite and a liquid hard carbon coating agent in a mass ratio of 100:10. The stirring speed of the fusion machine is 600 r / min, the stirring time is 7 min, and the liquid hard carbon coating agent is a commercially available liquid phenolic resin with a weight average molecular weight of 580, a viscosity of 550 mPa·s at 25°C, and a solid content of 70%-71%. The product after solid-liquid fusion is placed in a track kiln, heated to 1150°C for carbonization treatment under a nitrogen atmosphere, and the heat preservation time is 6 hours. Then the product is cooled to 50°C and taken out of the kiln. After depolymerization, screening and demagnetization treatment, a negative electrode active material is obtained.
[0308] Example 7
[0309] The preparation process of the battery is the same as that of Example 1 except that the preparation process of the negative electrode active material is different.
[0310] (1) Preparation of negative electrode active materials
[0311] The petroleum needle coke is crushed, shaped and graded to obtain aggregate; the obtained aggregate is mixed with binder asphalt in a mass ratio of 100:8 and placed in a horizontal reactor for heating and granulation. A step-by-step heating and insulation process is adopted during heating. The program temperature platforms are set to 200°C, 300°C, and 600°C, respectively. The temperature is kept constant at 200°C for 1h, 300°C for 2h, and 600°C for 2h, and then taken out of the furnace after cooling for 3h; the granulated material is placed in an Acheson graphitization furnace for graphitization at 3000°C for about 50h to obtain graphite.
[0312] A fusion machine is used to fuse graphite and a liquid hard carbon coating agent in a mass ratio of 100:0.7. The stirring speed of the fusion machine is 600r / min, the stirring time is 7min, and the liquid hard carbon coating agent is a commercially available liquid phenolic resin with a weight average molecular weight of 580, a viscosity of 550mPa·s at 25°C, and a solid content of 70%-71%. The product after solid-liquid fusion is placed in a track kiln, heated to 1150°C for carbonization treatment under a nitrogen atmosphere, and the heat preservation time is 6h. Then the product is cooled to 50°C and taken out of the kiln. After depolymerization, screening and demagnetization treatment, a negative electrode active material is obtained.
[0313] Table 4
[0314]
[0315] It can be seen from the test results in Table 4 that, under the same other conditions, adjusting the mass ratio of graphite to liquid hard carbon coating agent can adjust the R value R50 of 50% of the cumulative distribution of negative electrode active materials and the degree of uncoating of negative electrode active materials.
[0316] It can also be seen from the test results in Table 4 that when the mass ratio of graphite to liquid hard carbon coating agent is between 100:3 and 100:7, the battery can better combine high energy density, high cycle capacity retention rate and high critical charge rate.
[0317] It can also be seen from the test results in Table 4 that as the mass of the liquid-phase hard carbon coating agent increases, the battery's cycle performance will further improve at the beginning, and as the mass of the liquid-phase hard carbon coating agent further increases, the battery's cycle performance will show a downward trend. This is because when the mass of the liquid-phase hard carbon coating agent is small, the coating layer formed is thinner, and at this time the coating layer can play a role in reducing the co-embedding phenomenon of the solvent, thereby improving the battery's cycle performance; and as the mass of the liquid-phase hard carbon coating agent continues to increase, the thickness of the coating layer increases, and due to the large number of pores and side reactions in the coating layer, the battery's cycle performance will show a downward trend.
[0318] Example 8
[0319] The preparation process of the battery is the same as that of Example 1 except that the preparation process of the negative electrode active material is different.
[0320] (1) Preparation of negative electrode active materials
[0321] The petroleum needle coke is crushed, shaped and graded to obtain aggregate; the obtained aggregate is mixed with binder asphalt in a mass ratio of 100:8 and placed in a horizontal reactor for heating and granulation. A step-by-step heating and insulation process is adopted during heating. The program temperature platforms are set to 200°C, 300°C, and 600°C, respectively. The temperature is kept constant at 200°C for 1h, 300°C for 2h, and 600°C for 2h, and then taken out of the furnace after cooling for 3h; the granulated material is placed in an Acheson graphitization furnace for graphitization at 3000°C for about 50h to obtain graphite.
[0322] A fusion machine is used to fuse graphite and a liquid hard carbon coating agent in a mass ratio of 100:5. The stirring speed of the fusion machine is 600r / min, the stirring time is 7min, and the liquid hard carbon coating agent is a commercially available liquid phenolic resin with a weight-average molecular weight of 800, a viscosity of 25°C of 2000mPa·s, and a solid content of 70%-71%. The product after solid-liquid fusion is placed in a track kiln, heated to 1150°C for carbonization treatment under a nitrogen atmosphere, and the heat preservation time is 6h. Then the product is cooled to 50°C and taken out of the kiln. After depolymerization, screening and demagnetization treatment, a negative electrode active material is obtained.
[0323] Table 5
[0324]
[0325] It can be seen from the test results in Table 5 that, under the same other conditions, adjusting the weight average molecular weight and / or viscosity of the liquid phase hard carbon coating agent can adjust the R value R50 of the cumulative distribution of the negative electrode active material to 50% and the degree of uncoating of the negative electrode active material. When the weight average molecular weight and / or viscosity of the liquid phase hard carbon coating agent is within a suitable range, the negative electrode active material can have a smaller degree of uncoating, and the battery can have a higher critical charge rate, thereby enabling the battery to have better fast charging performance.
[0326] Example 9
[0327] The preparation process of the battery is the same as that of Example 1 except that the preparation process of the negative electrode active material is different.
[0328] (1) Preparation of negative electrode active materials
[0329] The petroleum needle coke is crushed, shaped and graded to obtain aggregate; the obtained aggregate is mixed with binder asphalt in a mass ratio of 100:8 and placed in a horizontal reactor for heating and granulation. A step-by-step heating and insulation process is adopted during heating. The program temperature platforms are set to 200°C, 300°C, and 600°C, respectively. The temperature is kept constant at 200°C for 1h, 300°C for 2h, and 600°C for 2h, and then taken out of the furnace after cooling for 3h; the granulated material is placed in an Acheson graphitization furnace for graphitization at 3000°C for about 50h to obtain graphite.
[0330] A fusion machine is used to fuse graphite and a liquid hard carbon coating agent in a mass ratio of 100:5. The stirring speed of the fusion machine is 350r / min, the stirring time is 7min, and the liquid hard carbon coating agent is a commercially available liquid phenolic resin with a weight average molecular weight of 580, a viscosity of 550mPa·s at 25°C, and a solid content of 70%-71%. The product after solid-liquid fusion is placed in a track kiln, heated to 1150°C for carbonization treatment under a nitrogen atmosphere, and the heat preservation time is 6h. Then the product is cooled to 50°C and taken out of the kiln. After depolymerization, screening and demagnetization treatment, a negative electrode active material is obtained.
[0331] Example 10
[0332] The preparation process of the battery is the same as that of Example 1 except that the preparation process of the negative electrode active material is different.
[0333] (1) Preparation of negative electrode active materials
[0334] The petroleum needle coke is crushed, shaped and graded to obtain aggregate; the obtained aggregate is mixed with binder asphalt in a mass ratio of 100:8 and placed in a horizontal reactor for heating and granulation. A step-by-step heating and insulation process is adopted during heating. The program temperature platforms are set to 200°C, 300°C, and 600°C, respectively. The temperature is kept constant at 200°C for 1h, 300°C for 2h, and 600°C for 2h, and then taken out of the furnace after cooling for 3h; the granulated material is placed in an Acheson graphitization furnace for graphitization at 3000°C for about 50h to obtain graphite.
[0335] A fusion machine is used to fuse graphite and a liquid hard carbon coating agent in a mass ratio of 100:5. The stirring speed of the fusion machine is 600 r / min, the stirring time is 5 min, and the liquid hard carbon coating agent is a commercially available liquid phenolic resin with a weight average molecular weight of 580, a viscosity of 550 mPa·s at 25°C, and a solid content of 70%-71%. The product after solid-liquid fusion is placed in a track kiln, heated to 1150°C for carbonization treatment under a nitrogen atmosphere, and the heat preservation time is 6 hours. Then the product is cooled to 50°C and taken out of the kiln. After depolymerization, screening and demagnetization treatment, a negative electrode active material is obtained.
[0336] Table 6
[0337]
[0338] It can be seen from the test results in Table 6 that, under the same conditions, adjusting the solid-liquid fusion parameters of graphite and the liquid phase hard carbon coating agent can adjust the degree of uncoating of the negative electrode active material. When the solid-liquid fusion parameters of graphite and the liquid phase hard carbon coating agent are within an appropriate range, the negative electrode active material can have a smaller degree of uncoating. When other conditions are the same, a small degree of uncoating of the negative electrode active material can make the battery have a higher critical charge rate, thereby making the battery have better fast charging performance.
[0339] Embodiment 11
[0340] Except for the different preparation process of the negative electrode plate, the preparation process of the battery is the same as that of Example 1.
[0341] (2) Preparation of negative electrode sheet
[0342] The negative electrode active material prepared in Example 1, thickener sodium carboxymethyl cellulose, negative electrode binder styrene-butadiene rubber (SBR), and negative electrode conductive agent Super P were mixed in a mass ratio of 96.9:1.1:1.5:0.5, and deionized water was added as a solvent. The mixture was stirred evenly under the action of a vacuum stirrer to prepare a negative electrode slurry.
[0343] The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, and the negative electrode current collector coated with the slurry is dried at room temperature and then transferred to an oven for drying, and then cold pressed and cut to obtain the negative electrode sheet. The thickness of the negative electrode film layer on one side of the negative electrode current collector is 58 μm.
[0344] Table 7
[0345] Serial number Critical charging rate Example 1 4.0C Embodiment 11 3.6C
[0346] It can be seen from the test results in Table 7 that by partitioning the negative electrode film layer and making the mass content of the first negative electrode active material in the first negative electrode film layer greater than the mass content of the second negative electrode active material in the second negative electrode film layer, and the mass content of the negative electrode binder in the first negative electrode film layer less than the mass content of the negative electrode binder in the second negative electrode film layer, the battery can have a higher critical charge rate, thereby making the battery have better fast charging performance. This is because the above-mentioned setting can reduce the floating problem of the negative electrode binder during the slurry drying process, thereby reducing the negative electrode binder content on the outer surface of the negative electrode film layer, which is beneficial to the liquid phase conduction of ions inside the negative porous electrode and the charge exchange of ions on the surface of the negative electrode active material, thereby making the battery have better fast charging performance.
[0347] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A negative electrode active material, characterized in that: The negative electrode active material includes a core and a coating layer located on at least a portion of the surface of the core, the core includes graphite, and the coating layer includes hard carbon; in the R value cumulative distribution curve of the negative electrode active material obtained in the surface scanning mode of the laser microscopic confocal Raman spectrometer, starting from the lower limit, the R value R50 with a cumulative distribution of 50% is 0.15-0.
40.
2. The negative electrode active material according to claim 1, characterized in that The cumulative distribution of the negative electrode active material has an R value R50 of 50% of 0.20-0.
30.
3. The negative electrode active material according to any one of claims 1 to 2, characterized in that: Among all R values obtained by the negative electrode active material, the number of R values R50 less than 50% of the cumulative distribution of the inner core accounts for less than or equal to 10%.
4. The negative electrode active material according to claim 3, characterized in that Among all R values obtained by the negative electrode active material, the number of R values R50 less than 50% of the cumulative distribution of the inner core accounts for less than or equal to 6%.
5. The negative electrode active material according to any one of claims 1 to 4, characterized in that: The R value R50 of the core at 50% of the cumulative distribution is less than the R value R50 of the coating layer at 50% of the cumulative distribution; and / or, The cumulative distribution of the coating layer is 50% of the R value R50 is 0.9-1.4; and / or, The cumulative distribution of the kernels has a 50% R value R50 of 0.06-0.
13.
6. The negative electrode active material according to any one of claims 1 to 5, characterized in that: The mass of the coating layer is 0.3%-4.5% of the mass of the core.
7. The negative electrode active material according to any one of claims 1 to 6, characterized in that: The mass of the coating layer is 1%-3.2% of the mass of the core.
8. The negative electrode active material according to any one of claims 1 to 7, characterized in that: The difference between the volume distribution particle size Dv50 of the negative electrode active material and the volume distribution particle size Dv50 of the core is 1 μm-5.5 μm; and / or, The volume distribution particle size Dv50 of the negative electrode active material is 8 μm-25 μm.
9. The negative electrode active material according to claim 8, characterized in that The difference between the volume distribution particle size Dv50 of the negative electrode active material and the volume distribution particle size Dv50 of the core is 1.5 μm-4.2 μm; and / or, The volume distribution particle size Dv50 of the negative electrode active material is 12 μm-17 μm.
10. The negative electrode active material according to any one of claims 1 to 9, characterized in that: The graphite is artificial graphite; and / or, The graphite is in the form of secondary particles; and / or, The intensity ratio C(004) / C(110) of the diffraction peak of the 004 crystal plane and the diffraction peak of the 110 crystal plane of the graphite measured by X-ray diffraction method is 5.5-6.5; and / or, The gram capacity of the negative electrode active material is 354 mAh / g-361 mAh / g; and / or, The compacted density of the negative electrode active material powder under a pressure of 20000N is 1.68g / cm 3 -1.78g / cm 3 and / or, The specific surface area of the negative electrode active material is 1.5 m 2 / g-4.5m 2 / g.
11. A method for preparing a negative electrode active material, characterized in that: The steps include: Providing coke raw materials; The coke raw material is crushed, shaped and classified to obtain aggregate; The obtained aggregate is mixed with a binder and granulated and graphitized in sequence to obtain graphite; The obtained graphite and the liquid hard carbon coating agent are solid-liquid fused; The solid-liquid fusion product is carbonized in a protective gas atmosphere so that the liquid phase hard carbon coating agent is carbonized into hard carbon and coated on at least part of the surface of the graphite to obtain a negative electrode active material. The negative electrode active material includes a core and a coating layer located on at least a portion of the surface of the core, the core includes graphite, and the coating layer includes hard carbon; in the R value cumulative distribution curve of the negative electrode active material obtained in the surface scanning mode of the laser microscopic confocal Raman spectrometer, starting from the lower limit, the R value R50 with a cumulative distribution of 50% is 0.15-0.
40.
12. The preparation method according to claim 11, characterized in that: The coke raw material includes one or more of petroleum-based needle coke and coal-based needle coke; and / or, The temperature of the graphitization treatment is 2800°C-3800°C; and / or, The mass of the liquid-phase hard carbon coating agent is 0.7%-10% of the mass of the graphite.
13. The preparation method according to claim 12, characterized in that: The temperature of the graphitization treatment is 2850°C-3300°C; and / or, The mass of the liquid-phase hard carbon coating agent is 3%-7% of the mass of the graphite.
14. The preparation method according to any one of claims 11 to 13, characterized in that: The liquid phase hard carbon coating agent comprises a liquid resin, the viscosity of the liquid resin at 25° C. is 150 mPa·s-2000 mPa·s, and the solid content of the liquid resin is 50%-85%.
15. The preparation method according to claim 14, characterized in that: The viscosity of the liquid resin at 25° C. is 300 mPa·s-900 mPa·s, and the solid content of the liquid resin is 60%-82%.
16. The preparation method according to any one of claims 14 to 15, characterized in that: The liquid resin includes at least one of liquid phenolic resin, liquid epoxy resin, liquid vinyl ester resin, liquid unsaturated polyester resin, liquid furan resin, and their respective derivatives.
17. The preparation method according to claim 16, characterized in that: The liquid phase hard carbon coating agent comprises liquid phenolic resin, and the solid content of the liquid phenolic resin is 60%-82% and the weight average molecular weight is 300-800.
18. The preparation method according to claim 17, characterized in that: The liquid phenolic resin has a solid content of 68%-78% and a weight average molecular weight of 450-700.
19. The preparation method according to any one of claims 11 to 18, characterized in that: The equipment for solid-liquid fusion of the graphite and the liquid hard carbon coating agent is a fusion machine, the stirring speed of the fusion machine is 350r / min-1000r / min, and the stirring time of solid-liquid fusion is 4min-10min; and / or, The heat preservation temperature of the carbonization treatment is 900°C-1500°C; and / or, The heat preservation time of the carbonization treatment is 2h-10h.
20. The preparation method according to claim 19, characterized in that: The stirring speed of the fusion machine is 450r / min-850r / min, and the stirring time of solid-liquid fusion is 6min-8min.
21. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, characterized in that: The negative electrode film layer comprises the negative electrode active material according to any one of claims 1 to 10 or the negative electrode active material prepared by the preparation method according to any one of claims 11 to 20.
22. The negative electrode sheet according to claim 21, characterized in that: The negative electrode film layer includes a first negative electrode film layer and a second negative electrode film layer located between the first negative electrode film layer and the negative electrode current collector, the thickness of the first negative electrode film layer is 30%-60% of the thickness of the negative electrode film layer, the first negative electrode film layer includes a first negative electrode active material, the second negative electrode film layer includes a second negative electrode active material, and the first negative electrode active material includes the negative electrode active material described in any one of claims 1-10 or the negative electrode active material prepared by the preparation method described in any one of claims 11-20.
23. The negative electrode sheet according to claim 22, characterized in that: The second negative electrode active material comprises the negative electrode active material described in any one of claims 1 to 10 or the negative electrode active material prepared by the preparation method described in any one of claims 11 to 20, the mass content w1 of the first negative electrode active material in the first negative electrode film layer is greater than the mass content w2 of the second negative electrode active material in the second negative electrode film layer; and / or, the mass content w1 of the first negative electrode active material in the first negative electrode film layer is greater than or equal to 96.9%, and the mass content w2 of the second negative electrode active material in the second negative electrode film layer is less than 96.9%.
24. The negative electrode plate according to claim 22, characterized in that: The second negative electrode active material includes graphite, the graphite is in a secondary particle morphology, and the cumulative distribution of the graphite has an R value R50 of 50% of 0.06-0.
13.
25. The negative electrode sheet according to claim 24, characterized in that: The mass content w1 of the first negative electrode active material in the first negative electrode film layer is greater than the mass content w2 of the second negative electrode active material in the second negative electrode film layer; and / or, the mass content w1 of the first negative electrode active material in the first negative electrode film layer is greater than or equal to 96.9%, and the mass content w2 of the second negative electrode active material in the second negative electrode film layer is less than 96.9%.
26. The negative electrode sheet according to any one of claims 21 to 25, characterized in that: The compaction density of the negative electrode film layer is 1.62 g / cm 3 -1.80g / cm 3 ; and / or, the thickness of the negative electrode film layer is 45μm-100μm.
27. The negative electrode sheet according to claim 26, characterized in that: The compaction density of the negative electrode film layer is 1.65 g / cm 3 -1.80g / cm 3 ; and / or, the thickness of the negative electrode film layer is 70μm-100μm.
28. A battery, characterized in that: Comprising the negative electrode sheet as described in any one of claims 21-27.
29. An electrical device, characterized in that: The battery of claim 28 is used to provide electrical energy.
Citation Information
Patent Citations
Cathode material of lithium ion battery and preparation method thereof
CN103199251A
Anode for lithium secondary battery and lithium secondary battery comprising the same
CN108878773A
Graphite-based negative electrode active material, preparation method and application thereof, and secondary battery
CN115312731A
Preparation method of graphite-based negative electrode material, graphite-based negative electrode material and application of graphite-based negative electrode material
CN115440959A
Composite graphite material and preparation method thereof, negative pole piece and secondary battery
CN115810724A
Cited By
Negative electrode active material and preparation method therefor, negative electrode sheet, lithium-ion battery, and electric device
EP4621877A1